2021
DOI: 10.3390/ijerph18063220
|View full text |Cite
|
Sign up to set email alerts
|

Social Ecological Model of Problem Gambling: A Cross-National Survey Study of Young People in the United States, South Korea, Spain, and Finland

Abstract: Problem gambling among young people is an emerging trend globally. The online environment in particular offers various possibilities for gambling engagement. This is the first cross-national survey study using the social ecological model to analyze problem gambling, especially in the online context. The study aimed to analyze how different social ecological spheres explain problem gambling. Participants were young people aged 15–25 in the United States (n = 1212), South Korea (n = 1192), Spain (n = 1212), and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 97 publications
(74 reference statements)
2
8
0
3
Order By: Relevance
“…We found that the number of good social relationships was a strong individual predictor of continuing treatment, which resonates well with earlier research: Having meaningful social relationships is beneficial not only for protection against problem gambling but also for better recovery from it, as well as adherence to treatment programs (Oksanen et al, 2021; Petry & Weiss, 2009). In the meta-analysis of Pfund et al (2021), being married was associated with lower dropout rates.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the number of good social relationships was a strong individual predictor of continuing treatment, which resonates well with earlier research: Having meaningful social relationships is beneficial not only for protection against problem gambling but also for better recovery from it, as well as adherence to treatment programs (Oksanen et al, 2021; Petry & Weiss, 2009). In the meta-analysis of Pfund et al (2021), being married was associated with lower dropout rates.…”
Section: Discussionsupporting
confidence: 90%
“…We also investigated differences in the relationships between the independent variables and excessive gambling in the four countries included in this study. In accordance with previous research, we expected that gambling behaviour among young people would be similar in different countries [ 37 ].…”
Section: Introductionsupporting
confidence: 85%
“…Este estudio mostró que entre un 5,6 y un 8,2% de los jóvenes participantes eran personas con problemas de juego y entre un 10,9 y un 12,6% jugadores en riesgo o transición. Estos datos son similares a los encontrados en España previamente con el SOGS-RA (6,3%) (Oksanen et al, 2021) e inferiores a los hallados con el DSM (17,6%) (Jiménez-Murcia et al, 2021). La mayoría de las personas clasificadas como jugadores con problemas o en riesgo/ en transición jugaban tanto a juegos de azar como estratégicos.…”
Section: Discussionunclassified